FORENSIC IMPLICATIONS OF CARPAL TUNNEL SYNDROME IN RELATION TO RADIOLOGICAL AND ORHOPEDITION - RASOOL, R; AFZAL , H; NOONARI, MA; KUMAR , P; RAJPAR, S; IMRAN, S (Biological and Clinical Sciences Research Journal, 2024)
Carpal tunnel syndrome (CTS) is a common peripheral neuropathy with significant clinical and forensic implications. The condition is characterized by compression of the median nerve within the carpal tunnel, leading to pain, tingling, and functional impairment. Accurate diagnosis is crucial not only for clinical management but also for forensic evaluations, especially in cases of occupational claims and medico-legal disputes. Objective: The purpose of this research is to investigate the forensic consequences of carpal tunnel syndrome regarding radiographic and ophthalmic examinations. Methods: This prospective study included 180 individuals, aged 18 to 65 years, of both genders. This study was conducted at the Department of Forensic Medicine LUMHS from January 2023 to June 2023. Group I comprised 90 patients diagnosed with CTS, while Group II included 90 individuals without CTS, serving as controls. Demographic data, including age, sex, and BMI, were recorded. CTS was confirmed using ultrasonographic and other diagnostic modalities. The cross-sectional area of the carpal tunnel at the pisiform (CSAp) and the carpal tunnel at the hook of the hamate (CSAc) was measured. Delta CSA was calculated as the difference between CSAc and CSAp. Sensitivity and specificity for CTS diagnosis were evaluated. Statistical analysis was performed using SPSS Version 26.0. Results: The study found a predominance of females in both groups, with 63 (70%) females in Group I and 58 (64.4%) in Group II. The mean age in Group I was 47.34 ± 8.58 years with a mean BMI of 25.13 ± 10.49 kg/m², while Group II had a mean age of 49.53 ± 12.74 years and a BMI of 26.34 ± 11.61 kg/m². Group I demonstrated significantly higher CSAc values (18.5 ± 3.35 mm²) compared to Group II (9.8 ± 7.25 mm²; p < 0.004). The delta CSA was also higher in Group I (7.37 ± 8.32 mm²) compared to Group II (1.3 ± 2.13 mm²; p < 0.005). The CSAp values showed no significant differences between groups (Group I: 9.4 ± 3.6 mm²; Group II: 7.12 ± 9.6 mm²). A delta CSA threshold of 2 mm² demonstrated high diagnostic accuracy, yielding a sensitivity of 99.1% and specificity of 100% for Group I wrists. Conclusion: Delta CSA is a highly reliable parameter for diagnosing CTS, surpassing CSAc in accuracy. Advanced ultrasonographic techniques, including high-frequency probes and enhanced power Doppler imaging, represent the gold standard for CTS diagnosis, providing robust evidence for both clinical and forensic applications.